(untitled) (Perspectivas em Ciência da Informação, 2009)
The recommended bibliographies references for the development of scientific research are those published by scientific journals. In spite of this recommendation, the use of not conventional documents is being increasing by undergraduate students. This paper, developed as a survey with 145 students in Administration, Accounting and Economics Sciences, characterizes the use these documents and analyzes teaching strategies supported in the use of not conventional documents.